Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s10072-011-0819-6
|View full text |Cite
|
Sign up to set email alerts
|

Burst firing transitions in two-compartment pyramidal neuron induced by the perturbation of membrane capacitance

Abstract: Neuronal membrane capacitance C (m) is one of the prominent factors in action potential initiation and propagation and then influences the firing patterns of neurons. Exploring the roles that C (m) plays in different firing patterns can facilitate the understanding of how different factors might influence neuronal firing behaviors. However, the impacts of variations in C (m) on neuronal firing patterns have been only partly explored until now. In this study, the influence of C (m) on burst firing behaviors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…The motivation to quantify the impact of c(f) on the firing rate of a pyramidal cell came from the findings of (Wang et al, 2012), who in a two compartment model of a pyramidal cell, observed great variation in the firing patterns of the cell by altering the (constant) capacitance of one or both compartments. In their model they defined quiescent, spiking, and bursting activity, and by introducing an imbalance between somatic and dendritic capacitance, the firing pattern transitioned between these states.…”
Section: Discussionmentioning
confidence: 99%
“…The motivation to quantify the impact of c(f) on the firing rate of a pyramidal cell came from the findings of (Wang et al, 2012), who in a two compartment model of a pyramidal cell, observed great variation in the firing patterns of the cell by altering the (constant) capacitance of one or both compartments. In their model they defined quiescent, spiking, and bursting activity, and by introducing an imbalance between somatic and dendritic capacitance, the firing pattern transitioned between these states.…”
Section: Discussionmentioning
confidence: 99%
“…However, altering the time course of the membrane potential dynamics will also alter the complex interplay between various depolarizing and hyperpolarizing membrane currents through active ion channels. Hence, the relationship between and f is not trivial, and will generally depend on the ion channels that a neuron possesses, as well as its input conditions (Szlavik, 2003 ; Wang et al, 2012 ).
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…In analyzing the transitions between different firing patterns, the diagram of interspike intervals (ISI) is introduced, which has been widely used to describe the transition modes among various firing behaviors in neurons [32][33][34][35]. The value of ISI is represented as the time difference between adjacent peaks within spike trains, which is illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the method we employed to describe the transition modes between different firing patterns is the ISI diagram, which has been widely used in the field of nonlinear analysis of neuronal systems [32][33][34][35]. Although widely applicable, and easy to be calculated numerically, ISI diagram has still failed to characterize the specific geometric structures of the corresponding bifurcation maps, thus for future considerations, other useful approaches, the phase plane analysis [59-50] and the fast/slow dynamical analysis [51][52][53] can be introduced to study the detailed bifurcation cascades like many other studies.…”
Section: Discussionmentioning
confidence: 99%